Contrasting impact of whole-tree-harvesting on chemical quality of plant foliage in coastal versus inland forest. Issue 6 (17th August 2016) - Fjære, Sigmund; Clarke, Nicholas; Nybakken, Line; Wam, Hilde Karine
ABSTRACT: Whole-tree-harvesting (WTH) is gaining support as a means to obtain more bioenergy from forests. One aspect that is scarcely addressed is its impact on the chemical quality of post-harvest plant growth, which may initiate ecological cascade effects through, for example, altered patterns of herbivory and decomposition. We measured C:N ratios and phenolic compounds in foliage from birch Betula spp. that had grown naturally after WTH and conventional harvest (CH) on two boreal sites in inland and more coastal Norway, three or five years after harvest. We found that carbon concentrations were higher after WTH compared to CH on the near-coastal site in spring and summer, but not on the inland site. The only observed change in nitrogen concentration after WTH was that it was lower compared to CH on the near-coastal site in autumn. In line with these changes, the C:N ratio was higher with WTH throughout the season on the near-coastal site, ostensibly favouring production or accumulation of plant defence metabolites. Expectedly, we observed altered concentrations of several phenolic compounds with WTH, particularly at the near-coastal site. Further studies are needed to clarify patterns, but our data strongly suggest that sustainability assessments of WTH should not ignore impact on plant chemical quality, and its potential consequences for trophic interactions.